THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN CARDIOLOGY ABSTRACT. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Artificial intelligence (AI) is playing an increasingly important role in the diagnosis, treatment, and monitoring of cardiovascular disease. This paper discusses the main applications of AI in cardiology, including electrocardiogram (ECG) analysis, prediction of cardiovascular interventions, and personalized patient care.